Ortner’s syndrome with primary pulmonary hypertension - a case report - Azwal, Norazwani; Muhammad, Athierah (2023)
Ortner’s Syndrome or Cardio-vocal syndrome is a manifestation of hoarseness secondary to left recurrent laryngeal nerve (RLN) palsy with abnormal cardiovascular components. The association of pulmonary hypertension with Ortner’s Syndrome has not been widely available in the literature with very few cases reported worldwide. We present a case of a 17 years old lady with underlying Primary Pulmonary Hypertension, who presented with progressive hoarseness over the past 3 years associated with breathlessness and easy fatigue on exertion. Herein we discuss the options of treatment modality for Ortner’s Syndrome.